RFID – Making It So…With Some Help From the University of Florida - Bruce A. Welt; Jean-Pierre Emond (EDIS)
Recent advances in passive radio frequency identification (RFID) technologies have inspired a revolution in thinking about supply chain and inventory management. Briefly, modern passive RFID involves “smart” labels, readers and associated transmitting and receiving antennas, and back-end computer control and database management systems. Figure 1 gives examples of typical RFID components. This document is Circular 1465, one of a series from the Department of Agricultural & Biological Engineering, UF/IFAS Extension. First published: March 2005.